Penggunaan Model STAD Berbantuan Media Biji Jagung Untuk Meningkatkan Hasil Belajar Bilangan Cacah Siswa Kelas III Sekolah Dasar - Ni Luh Putu Sri Marsia; I Made Sujana Adnyana (STKIP Subang, 2026)
This study is motivated by low mathematics learning outcomes in whole number material among third-grade elementary school students. This issue is caused by the use of less varied teaching methods and limited use of concrete objects, which results in low student engagement and difficulty in understanding abstract concepts. This study aims to improve students learning outcomes through the application of the Student Team Achievement Divisions (STAD) learning model assisted by concrete objects. The STAD model encourages students to work in groups, help each other, and actively participate in learning. Meanwhile, concrete objects help students understand whole number concepts in a more real and meaningful way according to their cognitive development stage. The method use is classroom action research conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects were 32 third-grade elementary school students. Data were collected using learning achievement tests and observation sheets. The results show an improvement in students learning outcomes in each cycle. In the first cycle, there was an increase compared to the initial condition, but the success criteria had not yet been achieved. After improvements in the second cycle, students learning outcomes increased significantly and met the expected mastery level, where at least 80% of students reached the minimum passing grade (KKTP). Therefore, if can be concluded that the STAD learning model assisted by concrete objects is effective in improving students learning outcomes in whole number material